Boric acid protects against cyclophosphamide-induced oxidative stress and renal damage in rats - Cengiz, Mustafa (Cellular and Molecular Biology, 2018)
The worldwide increase in the rate of cancer incidence also leads to a significant increase in the use of chemotherapeutic agents. Unfortunately, the optimal clinical usefulness of these agents is heavy restricted by a high incidence of several organ toxicity and as well reason oxidative stress and bring about changing in antioxidant status. Kidney toxicity is a side effect often encountered with cyclophosphamide (CPM) which is commonly used in most cancer chemotherapy. The present study aims on the assessment of the probable defensive efficacy of Boric acid (BA) against CPM-induced oxidative stress and renal damage in rats. Based upon our investigation results with oxidative stress markers and light microscopic findings, it can be concluded that BA significantly reduced CPM induced oxidative stress and renal damage. As far as we know, high dose (200 mg/kg) of BA are the first study on the prevention of kidney damage caused by CPM. It is thought that the renoprotective effects of BA may be due to an increase in the activity of the antioxidant protection system and also inhibition of lipid per oxidation.